2023
DOI: 10.1111/1750-3841.16433
|View full text |Cite
|
Sign up to set email alerts
|

Sodium reduction in foods: Challenges and strategies for technical solutions

Abstract: In many parts of the world, sodium consumption is higher than recommended levels, representing one of the most important food-related health challenges and leading to considerable economical costs for society. Therefore, there is a need to find technical solutions for sodium reduction that can be implemented by food producers and within food services. The aims of this review are to discuss the barriers related to sodium reduction and to highlight a variety of technical solutions. The barriers relate to consume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 127 publications
(129 reference statements)
0
6
0
Order By: Relevance
“…The second most mentioned category from the WA task was bland and many participants stated that SRFs are bland or taste healthy. This result identifies the main challenge faced in the food industry, as many studies have found that SRFs have a bland flavour when compared to their conventional counterpart (Halim et al ., 2020; Vinitha et al ., 2022; Lorén et al ., 2023). Also, a food labelled as salt‐reduced can impact consumer acceptance as well (Kongstad & Giacalone, 2020; Gorman et al ., 2023).…”
Section: Resultsmentioning
confidence: 99%
“…The second most mentioned category from the WA task was bland and many participants stated that SRFs are bland or taste healthy. This result identifies the main challenge faced in the food industry, as many studies have found that SRFs have a bland flavour when compared to their conventional counterpart (Halim et al ., 2020; Vinitha et al ., 2022; Lorén et al ., 2023). Also, a food labelled as salt‐reduced can impact consumer acceptance as well (Kongstad & Giacalone, 2020; Gorman et al ., 2023).…”
Section: Resultsmentioning
confidence: 99%
“…99 Reducing the salt content in food poses three significant challenges, namely sensory perception, microbiological concerns, and structural and textural alterations. 100 Therefore, the direct reduction of salt content in food proves to be a challenging task. Extensive research has been conducted to achieve the objective of reducing salt while preserving the physicochemical properties, sensory characteristics, and microbial stability of food (Fig.…”
Section: Salt Reduction Strategies Of Foodmentioning
confidence: 99%
“…The rate of salt crystal dissolution in the oral cavity is significantly influenced by its crystal habit, which is often referred to as the morphology of the crystalline solid. 100,154 The solubility of crystals often varies between different forms. 155 Quilaqueo et al investigated the dissolution of five different forms of commercial salts (Fig.…”
Section: Morphology and Porositymentioning
confidence: 99%
“…The strategies that are most frequently used include the reduction in added salt in formulations and the replacement of sodium chloride by alternative salts containing less or no sodium (e.g., KCl, MgCl 2 , CaCl 2 ) or being structurally modified. Moreover, the addition of alternative ingredients such as flavour enhancers, e.g., herbs, spice seasonings and yeast extracts, and textural agents or the use of different processes are also part of the industrial strategies to favour a decrease in the sodium content of processed foods [ 11 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. As described in Table 1 , they can promote concrete solutions for a variety of foods.…”
Section: Potential Contribution Of the Food Industrymentioning
confidence: 99%